Evaluating the potential for an increased and sustainable commercial fisheries production across multiple jurisdictions and diverse fisheries. (February 2021) - Smith, David C.; Haddon, Malcolm; Punt, André E.; Gardner, Caleb; Little, L. Richard; Mayfield, Stephen; O'Neill, Michael F.; Saunders, Thor; Stewart, John; Wise, Brent; Fulton, Elizabeth A.; Conron, Simon
Abstract: We describe a first estimate of the potential to increase production from Australia's commercial fisheries based on the difference between current catches and maximum sustainable yield (MSY). MSY is not being advocated as a target reference point but enables a level of consistency across species and/or jurisdictions with different reference points. MSY estimates were obtained for 290 species/stocks that comprised 84% of annual landings. 75% of the estimates were computed using methods applied specifically for this study, aided by an assessment framework, and supporting software. The catch-MSY method was used extensively given the lack of formal assessments for many species, and the limitations of taking this approach are discussed. The results indicated that potential production could be more than double the current national catch (an increase over current catches of about 124%), but potential increases varied considerably among Federal, State and Territory jurisdictions. The potential for increased production was particularly influenced by predictions for highly productive small pelagic fishes, although ignoring the potential for increased catches of these species still led to an estimate of an increase of almost 80% over current catches. Other factors such as whether an increase in production has market demand are also clearly important, along with other social and economic issues. Impacts on ecosystem sustainability and the consequences of climate change were beyond the scope of this study and would need to be considered in separate analyses. However, in making our estimates of potential production we acknowledged the issues with attempting to use single species approaches to provide fish community wide estimates and acted conservatively with our interpretation. Consequently, the results presented in this paper provide useful insights into possible biologically sustainable catches and the potential for increased production. Highlights: The potential for an increase in total commercial fisheries production across multiple jurisdictions and fisheries in Australia. Maximum sustainable yield was estimated for 290 species/stocks comprising 84% of total landings. Potential production could be doubled and, accounting for small pelagic species, an increase in production of almost 80% is possible. Increases depend on the target reference points used in the management and the depletion level of each species/stock. Further research would be required to evaluate market demand and environmental implications.